Fulminant Immune-Mediated Necrotising Myopathy with Multi-Organ Failure in a Previously Healthy Adult: A Case Report - Ramanan Sampavi; Namal Chathuranga Herath; Tharindu Sisilarathna; Chaminda Gunathilaka; Hemal Senanayake (Journal of Tropical Health, 2026)
Immune-mediated necrotizing myopathy (IMNM) is a severe inflammatory myopathy characterized by rapidly progressive weakness, markedly elevated creatine phosphokinase (CPK) levels, and myofiber necrosis with minimal inflammatory infiltrates. Early diagnosis is essential due to the risk of respiratory compromise, systemic involvement, and multi-organ dysfunction.This case highlights the fulminant behaviour of idiopathic IMNM, the diagnostic complexity in seronegative patients, and the importance of considering IMNM in adults presenting with acute flaccid paralysis, severe CPK elevation of 4,238,500 U/L, and preserved reflexes. Early recognition and rapid immunosuppression are essential to prevent catastrophic complications.